2007
DOI: 10.1159/000102592
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Varicocele on Electrical Field Stimulation-Induced Biphasic Twitch Responses in the Ipsilateral and Contralateral Rat Vasa Deferentia

Abstract: Aim: Although little is known about the mechanisms, varicocele is considered as one of the factors leading to male infertility. Since reduced motility of the vas deferens was shown to contribute to male infertility, in this study we aimed to investigate the effect of varicocele on electrical field stimulation (EFS)-induced biphasic contractions of the vas deferens in order to evaluate the effect of varicocele on the motility of the vas deferens. Material and Methods: A total of 26 Sprague-Dawley rats (200–250 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Although vas deferens motility was not traditionally thought to be associated with varicocele, Ozen et al [28] have documented a novel effect of varicocele on vas deferens motility, at least in a rat model. In a recent study, they demonstrated decreased contractile response in the ipsilateral vas deferens compared with the contralateral vas in rats with induced varicoceles.…”
Section: Other Novel Changes Associated With Varicocelementioning
confidence: 99%
See 1 more Smart Citation
“…Although vas deferens motility was not traditionally thought to be associated with varicocele, Ozen et al [28] have documented a novel effect of varicocele on vas deferens motility, at least in a rat model. In a recent study, they demonstrated decreased contractile response in the ipsilateral vas deferens compared with the contralateral vas in rats with induced varicoceles.…”
Section: Other Novel Changes Associated With Varicocelementioning
confidence: 99%
“…In 2005, Nicotina et al [27] showed increased expression of aquaporin receptor-1 (AQP-1) on venular endothelial cell membranes and in the cell membrane of Sertoli cells, diploid germ cells, and haploid cells in patients with varicocele. This may suggest that in the setting of varicocele, the testis is attempting to overcome fluid imbalance in the tubular and interstitial compartments.Although vas deferens motility was not traditionally thought to be associated with varicocele, Ozen et al [28] have documented a novel effect of varicocele on vas deferens motility, at least in a rat model. In a recent study, they demonstrated decreased contractile response in the ipsilateral vas deferens compared with the contralateral vas in rats with induced varicoceles.…”
mentioning
confidence: 99%
“…In an earlier study, Ozen et al [8] found that the varicocele significantly inhibited the ''either'' phases of EFS induced biphasic contractions in the ipsilateral side. Their study suggested that the varicocele has caused damages in the presynaptic area and affected vas deferens motility.…”
Section: Discussionmentioning
confidence: 94%
“…There is limited data in the literature investigating the effects of varicocele on the vas deferens motility [8]. The aim of this study is to evaluate not only the motility defects of vas deferens for the period of varicocele, but also the effects of surgical varicocele correction on the vas deferens motility.…”
Section: Introductionmentioning
confidence: 99%
“…In conjuction with this study, Gur et al (2010) also demonstrated that rats co-treated with sildenafil and L-NAME reversed this EFS and α−β-methylATP hypercontractile property of the vas deferens. Additionally, a varicocele model has resulted in a decrease vas contractile response (Ozen et al, 2007). Taken together, alterations in vas are clinically applicable, and may have implications for fertility, ejaculation abnormalities, and possibly vasectomy associated pain (Granitsiotis and Kirk, 2004; Tandon and Sabanegh, 2008).…”
Section: Signal Transductionmentioning
confidence: 99%